2015
DOI: 10.1556/jfc-d-14-00038
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up the Throughput of Synthesis and Extraction in Droplet Microfluidic Reactors

Abstract: Conducting reactions in droplets in microfluidic chips offers several highly attractive characteristics, among others, increased yield and selectivity of chemical syntheses. The use of droplet microfluidic systems in synthetic chemistry is, however, hampered by the intrinsically small throughput of micrometric channels. Here, we verify experimentally the potential to increase throughput via an increase of the scale of the channels. We use the results of these experiments characterizing the processes of (1) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…[67] Fortunately, this problem can be solved by parallelizing a large number of microfluidic cell encapsulation units or channels onto a single chip or chipset. [68, 69] Mulligan et al successfully developed a single microfluidic chip consisting of six microfluidic flow-focusing units operating in parallel to achieve a production rate of hundreds of milliliters per hour. [68] Considering the possibility of parallelizing a large number of microfluidic chips with multiple flow-focusing units, the production rate could even be improved.…”
Section: Discussionmentioning
confidence: 99%
“…[67] Fortunately, this problem can be solved by parallelizing a large number of microfluidic cell encapsulation units or channels onto a single chip or chipset. [68, 69] Mulligan et al successfully developed a single microfluidic chip consisting of six microfluidic flow-focusing units operating in parallel to achieve a production rate of hundreds of milliliters per hour. [68] Considering the possibility of parallelizing a large number of microfluidic chips with multiple flow-focusing units, the production rate could even be improved.…”
Section: Discussionmentioning
confidence: 99%
“…It is further noted that the droplet owing in a microuidic channel exhibits intensive mixing as a result of eddy pairs inside the volume. 48 Thereby, droplet should have the same concentration of oxygen in the entire volume, as well as at the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, several reports have recently shown that one possible way to overcome this challenge is to parallelize a large number of microfluidic cell encapsulation units and networks of microchannels onto a single chip, or a chipset (Korczyk et al, 2015; Mulligan and Rothstein, 2012; Tendulkar et al, 2012). In this way, widespread utilization of the microfluidics for cryopreservation is entirely feasible.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%